OPTIMIZATION OF MUNICIPAL SOLID WASTE COLLECTION SYSTEM IN HEFEI CITY OF CHINA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The refuse collection spot is the central part in the municipal solid waste collecting system. The wrong collecting way would lead to environmental problem and disturb the life of citizens. With the demand of source separation in China, the waste collecting sites need to be improved. Nowadays there have three different types of wastes collecting in Hefei, capital city in Anhui province, China. The advantages and disadvantages of such waste collection system were compared and discussed. The suggestions were put forward. Concerning about special example for agricultural market waste collection, taking Hefei Wanguo market as a sample, the research was made to optimize the present collection system. Compared with traditional waste collecting sites, the results showed the agricultural market waste collecting sites were better in both environmental and social efficiency.